Mass-spring models for the simulation of mitral valve function: Looking for a trade-off between reliability and time-efficiency. (September 2017) - Pappalardo, O.A.; Sturla, F.; Onorati, F.; Puppini, G.; Selmi, M.; Luciani, G.B.; Faggian, G.; Redaelli, A.; Votta, E.
Highlights: Patient-specific mass spring modeling (MSM) of the mitral valve (MV) from cardiac magnetic resonance (cMR) imaging. Quantitative comparison of MSM accuracy and computational cost vs. state-of-the-art finite element MV models. MSM simulation of MV closure including the patient-specific cMR-derived annular kinematics and papillary muscles motion. Differentiation of the anisotropic and non-linear mechanical response of the anterior and posterior MV leaflets. Abstract: Patient-specific finite element (FE) models can assess the impact of mitral valve (MV) repair on the complex MV anatomy and function. However, FE excessive time requirements hamper their use for surgical planning; mass-spring models (MSMs) represent a more approximate approach but can provide almost real-time simulations. On this basis, we implemented MSMs of three healthy MVs from cardiac magnetic resonance (cMR) imaging to simulate the systolic MV closure, including the in vivo papillary muscles and annular kinematics, and the anisotropic and non-linear mechanical response of MV tissues. To test MSM reliability we compared the systolic peak configurations computed by MSMs and FE: mismatches by less than twice the in-plane cMR image resolution were detected over 75% of the leaflets' surface, independently of the MSM mesh refinement and of the specific MV anatomy. Data on MSMs time-efficiency and data from the comparison of MSMs vs. FE models suggest that MSM could represent a suitable trade-off between almost real-time simulations and reliability when computing MV systolic configuration, with the potential to be used in a clinical setting either as a support to the decisional process or as a virtual training tool.